Secondary Socialization of Homeschoolers during the Covid-19 Pandemic - Václav Šimek; Albert Oláh; Kateřina Bočková (Emerging Science Journal, 2021)
The presented article deals with the description of the socialization of basic school pupils, i.e. pupils in younger and middle school age, who fulfill the compulsory school attendance in the form of individual education (homeschooling) in the context of the legislation of the Czech Republic. In the context of fulfilling the article aim, we formulated three research questions, which were evaluated using quantitative research in the form of a questionnaire survey. The research confirmed that parents of homeschoolers significantly support their children in participating in organized leisure activities and are actively involved in mediating their child's contact with other children. In the comparison of the examined groups there were no significant differences in how the children perceive their friends, what their favorite activities are or how much time they spend with them. The difference was more noticeable in the parental approach in education, when setting some rules. This article can outline areas that can be further explored in more detail and compared in context. Doi: 10.28991/esj-2021-SPER-12 Full Text: PDF